Efeitos Cardiovasculares e Respiratórios do Tratamento com Captopril em Ratos Submetidos à Hipertensão Arterial Pulmonar com Monocrotalina - Pascoal, Veronica Lourenço Wittmer (2014)
Background: Pulmonary Arterial Hypertension (PAH) is a disease associated with increased arteriolar resistance in the lungs. Due to hypoxemia, some physiological mechanisms can be posteriorly affected, including respiratory and cardiovascular reflexes, but this has not yet been fully investigated. This study aimed to evaluate how these mechanisms were affected by monocrotaline (MCT)-induced PAH and the possible therapeutic role of angiotensin converting enzyme inhibitor (ACEi), captopril, in reversing this remodeling process. Methods and Results: Groups of wistar rats received MCT injections (60 mg.kg-1 ). Three weeks later, they received captopril (CPT, 100 mg.kg-1) in their drinking water (MCT+CPT) or water alone (MCT) for 2 weeks. As control, saline-treated animals received CPT in their drinking water (CPT) or water alone (CON), also for 2 weeks. Results showed that PAH was fully induced in the MCT group, evidenced by a high pulmonary index. Gasometrical and respiratory analyses showed hypoxemia and compensatory hyperventilation. CPT treatment brought these parameters to similar values to those observed in the CON group. We observed that autonomic dysfunction in the MCT group was suppressed by CPT. Finally, cardiovascular reflexes analysis showed increased chemoreflex responses in the MCT group, while baroreflex and Bezold-Jarisch reflex sensibility was decreased. Surprisingly, CPT normalized these reflex responses to values similar to the CON group. Conclusions: The present study demonstrates that MCT-induced PAH induces compensatory respiratory responses, dysautonomia, baroreflex and Bezold-Jarisch reflex dysfunction and increases chemoreflex responses. The data also indicate that CPT was effective in reversing these cardio-respiratory disorders, suggesting that ACEI could be a potential therapeutic target for PAH.